Stress, Social Support, and Psychosocial Functioning of Ethnically Diverse Students. Issue 3 (5th October 2017) - Farrell, Michelle; Langrehr, Kimberly J.
Abstract : This study examined the stress‐buffering role of social support on indicators of psychosocial functioning among a combined and split sample of ethnically diverse college students. Although high social support significantly moderated 2 relationships in the combined sample, high and low levels of social support significantly reduced the effect of stress on depressive symptoms of students of color. For White students, high social support moderated the effect of stress on protective behaviors. Implications for college counselors are discussed.